Measurement of development with human security in Sonora between 2005 to 2020 - Acuña Méndez, Francisco (Posgrados de la División de Ciencias Económica Administrativas, 2023)
The measurement of traditional development is usually through conventional methods such as economic development measured by the human development index, or by GDP per capita; a social development measured by poverty indices, or access to health services. The article does not discuss existing development theories, but makes a theoretical and quantitative effort to combine development theories with the concept of human security. At the same time, it takes up a measurement of development that, given certain standards, can then be referred to as “development with human security”. In this sense, the objective of the article deals with the construction of an instrument to measure this concept. As can be seen, the case of Sonora is from 2005 to 2020, with advances in certain sectors, but setbacks in others, and this leads to comprehensive development, or development with human security, that registers the same level in that period of time.